Interface : altering architecture : transforming existing mono-functional buildings in the Pretoria CBD to adapt to changing social spatial conditions. The notion of ‘altering architecture’ aims to manipulate existing boundaries into INTERFACES to affect interior spaces and building skins as well extend into the urban context - Van der Wath, Elana (University of Pretoria, 2013)
Dissertation (MInt(Prof))--University of Pretoria, 2010.